The Analysis of Exposure Welding Fumes with Impaired Lung Faal Workers Welding PT. PAL Indonesia (Persero) - Riesa Desy; Lilis Sulistyorini (JURNAL KESEHATAN LINGKUNGAN, 2017)
Welding is an activity that has a major risk for lung function disorders resulting from gas and fumes generated. The general objective of this study was to analyze the overview of fumes exposure, individual characteristics with impaired lung function welding workers in PT. PAL INDONESIA (Persero). The type of this research is an observational study and is descriptive with cross sectional approach. The sample used the total population of the labor of welding PT. PAL INDONESIA (Persero). Measuring levels of fumes using HVDS, measurements were performed on a 4 point welding workshop. Examining of lung function is done by using a spirometer. And the risk factor data obtained from questionnaires and interviews. The results of this study showed levels of fumes that exceed 2 NAB contained in welding workshop From the results of pulmonary function measurement, there are three workers with impaired lung function by the category of mild obstruction and restriction. Characteristics of individuals who have an influence on the occurrence of pulmonary function disorders worker is of masks used by workers. Welding workers should wear masks that have been provided by PT. PAL INDONESIA. PT. PAL INDONESIA should undertake an obligation to conduct periodic health for workers.